Analisis Kelayakan Penggunaan Tameng Bertegangan Rendah dalam Penanganan Konflik Sosial: Kajian Aspek Keselamatan dan Efektivitas pada Kompi 1 Yon B Pelopor Brimob di Kabupaten Sumbawa Besar - Arie Prima; Muhamad Hidayat (LPPM Institut Pendidikan Nusantara Global, 2026)
Research on Public Order Control (PHH) shields has generally focused on material strength, impact resistance, and ergonomic design as passive protective equipment. However, studies integrating shatter-resistant materials, high impact resistance, and low-voltage technology into a single protective system to enhance both personnel safety and crowd-control effectiveness remain limited. This research gap indicates the absence of comprehensive investigations evaluating the feasibility of low-voltage shields from the perspectives of user safety, operational effectiveness, and compliance with the Indonesian National Police's (POLRI) use-of-force principles. Therefore, this study examines the feasibility of implementing low-voltage shields for Company 1, Battalion B Pelopor, Mobile Brigade Corps (Brimob), in Sumbawa Besar Regency, with particular emphasis on the shields' ability to provide optimal protection through shatter-resistant materials, superior impact resistance, and a non-lethal low-voltage electric shock mechanism to support safer and more effective social conflict management. This research employs a qualitative-descriptive approach using a case study strategy, with data collected through in-depth interviews, field observations, and documentation. The Technology Acceptance Model (TAM) developed by Davis (1989) is used as the analytical framework with three main constructs: Perceived Usefulness, Perceived Ease of Use, and Actual System Use. The results reveal high levels of perceived usefulness and ease of use among all seven informants, though actual implementation has not yet been carried out due to the absence of specific regulations and standardized testing. The study concludes that low-voltage shields are technically and operationally feasible as an innovative PHH equipment for Brimob personnel in handling social conflicts in Sumbawa Regency, provided that technical standards, SOP formulation, special training, and institutional legalization are fulfilled.